Membangun Jiwa Kewirausahaan Masyarakat Pekon Klaten Melalui Pemanfaatan Lahan Sempit - Lies Kumara Dewi; Eka Ubaya Taruna Rauf; Husna Purnama; Patoni Patoni (Empowerment: Jurnal Pengabdian Masyarakat, 2022)
This entrepreneurship program is to provide recommendations or alternative solutions to a problem how to build the entrepreneurial spirit of the community through the use of narrow land, namely hydroponic planting in Pekon Klaten, Gading Rejo District, Pringsewu Regency, Lampung Province. This partnership program activity aims to 1) Provide assistance to overcome problems that arise from the establishment of "Entrepreneurship" SMEs. 2) Conducting education and training for people who manage Hydroponics. 3) Involving Professional Trainers to provide guidance to the managers of SMEs "Entrepreneurship". 4) Provide the facilities and infrastructure needed in the development of the Hydroponics business. The external forms include 1) Increasing public understanding of hydroponic farming techniques so that they can be more effective and efficient. 2) Improving the ability of the community to be able to develop their business on a wider scale. 3) Improving the ability of the community in the field of marketing through social media. 4) Scientific publications. The implementation methods include 1) Management Training. 2) Hydroponic Innovation Training. 3) Bookkeeping and Financial Reporting Training. 4) Assistance and Consultation. 5) Training on the Use of Media/tools.